Nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst as well as preparation method and application thereof

The Fe3O4 catalyst is coated with porous carbon chamber co-doped with nitrogen and sulfur. The problem of slow Fe ion leaching and degradation speed of Fe ion when activated persulfate catalytic degradation of Locksamide is solved, and efficient and stable catalytic effect is achieved. Good cycle performance.

CN119114134APending Publication Date: 2024-12-13SHENYANG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411264706.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing Fe3O4 catalysts have Fe ion leaching problems when activating persulfate catalytic degradation of Locksamide, slow degradation speed, high magnetic properties and surface energy, resulting in a decrease in active sites, which limits its wide application.

Method used

The Fe3O4 catalyst is coated with a porous carbon chamber co-doped with nitrogen and sulfur, and prepared by hydrothermal method and pyrolysis method to form the Fe3O4@NS4C catalyst. The catalytic activity is improved by using the confined domain effect of the carbon support and the synergistic effect of heteroatom doping. and stability.

Benefits of technology

The good magnetic properties of Fe3O4@NS4C catalyst are achieved for easy recovery, with fast degradation rate, high degradation efficiency, good cycle stability, and can achieve a 95.1% degradation rate of Locksamide within 30 minutes, and the catalytic performance is basically restored after thermal regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114134A_ABST
    Figure CN119114134A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of wastewater treatment, and relates to a nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst as well as a preparation method and application thereof. Comprising the following steps: (1) dissolving ferric sulfate heptahydrate, hexamethylenetetramine and glucose in deionized water, and uniformly stirring and mixing to form a solution a; dissolving thiophenedicarboxylic acid in N, N-dimethylformamide, and uniformly stirring and mixing to form a solution b; dropwise adding the solution b into the solution a, and uniformly stirring and mixing to form a mixed solution; (2) carrying out hydrothermal reaction on the mixed solution, cooling to room temperature, filtering, washing, centrifuging and drying to obtain a Fe3O4-coated NS4C precursor; and (3) carrying out pyrolysis on the Fe3O4 (at) NS4C precursor to obtain the Fe3O4 (at) NS4C catalyst. The catalyst prepared by the method has good magnetism, high degradation rate, high degradation efficiency and good cycle stability, and has a good application prospect in activated persulfate catalytic degradation of ROX.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wastewater treatment, and specifically relates to a nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst and a preparation method and application thereof. Background Art

[0002] Roxarsone (4-hydroxy-3-nitrophenylarsonic acid, ROX) is an organic arsenic feed additive that can be converted into highly toxic inorganic arsenic through biotransformation and photolysis in the natural environment.

[0003] Persulfate (PMS) activation of heterogeneous catalysts is an effective means to treat ROX. Iron is the fourth most abundant element in the earth's crust and is recognized as a non-toxic, efficient and economical catalyst for activating PMS. However, Fe 3+ / Fe 2+ (+0.77V) has a low reduction potential and poor conductivity, resulting in Fe 2+ The regeneration ability of Fe3O4 is poor, and Fe3O4 has certain magnetism and high surface energy, which makes it easy to agglomerate during the catalytic process, resulting in a reduction in active sites. The above restrictive factors affect the catalytic efficiency of Fe3O4 to activate PMS. In addition, there are also many reports that it has serious metal ion leaching problems. These drawbacks have greatly limited the widespread application of Fe3O4 as a catalyst.

[0004] In order to improve the performance of Fe3O4 catalyst to activate PMS, researchers have done a lot of work, among which one of the more effective means is to make nanocomposites by fixing Fe3O4 nanoparticles. Fixing Fe3O4 nanoparticles on a specific carrier effectively limits the Fe ion leaching of Fe3O4 nanoparticles, improves the stability of the material, and maintains the dispersibility of Fe3O4 nanoparticles to a certain extent. For example, Su Shanshan from East China Normal University studied the degradation-adsorption of roxarsone by iron-based nanocomposites catalyzed by persulfate or hydrogen peroxide. A composite material was prepared by impregnating reduced graphene oxide and carbon nanotubes with goethite, and an iron-based metal organic framework MIL-101 (Fe) was synthesized by hydrothermal method as a dual-functional agent for catalysis and adsorption of ROX. However, its catalytic reaction time is long and the degradation of the structure of roxarsone can only be achieved under the irradiation of ultraviolet-visible light. Summary of the invention

[0005] In view of the above-mentioned defects in the prior art, the present invention provides a nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst and a preparation method and application thereof. The prepared nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst has good magnetic properties and is easy to recover; it has a fast degradation rate, high degradation efficiency and good cycle stability, and has good application prospects in the activated persulfate catalytic degradation of ROX.

[0006] The technical objectives of the present invention are achieved through the following technical solutions:

[0007] In a first aspect, the present invention provides a nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst, comprising: a N, S co-doped porous carbon chamber, and Fe3O4 loaded in the pores and on the surface of the porous carbon chamber.

[0008] In some other embodiments, the specific surface area of ​​the carbon chamber is 45.281 m 2 / g, pore size 3.94nm.

[0009] The inventors found in the course of their research that carbonaceous materials are widely used as carriers of metal oxides due to their unique microstructure, adjustable geometric dimensions and variable morphology. The significant electronic metal-carrier interaction caused by the coupling of metal nanoparticles and carbon carriers can effectively adjust the electronic structure of the catalytic material and shorten the mass transfer distance, thereby increasing the rate of PMS activation and degradation of organic pollutants. By adjusting the structure of the chemical reaction at the nanoscale and encapsulating the chemical reaction in a specific confined space (such as multi-shell hollow microspheres, carbon nanotubes, etc.), a unique confinement effect can be exerted, the mass transfer distance can be shortened, and a selective reaction to pollutants can be achieved.

[0010] In order to further enhance the catalytic activity of metal-carbon materials, heteroatoms (N, P, S, B, etc.) are doped into the carbon skeleton to adjust the electronic and chemical properties of the carbon matrix. The electronegativity of N atoms (3.04) is greater than that of C (2.55). Therefore, the composite material of N-doped carbon supporting metal (M) has an adjustable surface charge distribution and a relatively stable MN bond, which helps to inhibit metal leaching during the degradation process. At the same time, N-containing functional groups can also promote the adsorption of organic compounds on the catalytic site, further improving the degradation performance of organic matter. S atom doping can change the asymmetric charge density and spin state of nearby carbon atoms, form defect sites, and improve the catalytic performance of carbon materials. S, N-co-doping of carbon carriers can lead to redistribution of electrons. Based on the synergistic effect of the two, better catalytic efficiency will be produced than carbon materials doped with N or S alone. Therefore, coating the modified carbon material on the outside of Fe3O4 can not only achieve the synergistic effect of Fe, N, S, and C, but also realize the function of confinement.

[0011] In a second aspect, the present invention provides a method for preparing the above-mentioned nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst, comprising the following steps:

[0012] (1) dissolving ferrous sulfate heptahydrate, hexamethylenetetramine, and glucose in deionized water, and stirring to form a solution a;

[0013] Dissolve thiophene dicarboxylic acid in N,N-dimethylformamide solution, and stir to form solution b;

[0014] Add solution b dropwise into solution a, and stir to form a mixed solution;

[0015] (2) subjecting the mixed solution to a hydrothermal reaction, cooling it to room temperature, filtering, washing, centrifuging, and drying to obtain a Fe3O4@NS4C precursor;

[0016] (3) The Fe3O4@NS4C precursor is pyrolyzed to obtain the Fe3O4@NS4C catalyst.

[0017] In some other embodiments, in step (1),

[0018] The molar ratio of ferric sulfate heptahydrate: hexamethylenetetramine: glucose: thiophenedicarboxylic acid is (1-1.5): (1-1.5): (0.78-0.8): (4-6);

[0019] Preferably, the molar ratio of ferric sulfate heptahydrate: hexamethylenetetramine: glucose: thiophenedicarboxylic acid is 1:1:0.78:4;

[0020] The stirring temperature of the mixed solution is 25-30° C., and the stirring time is 30-60 min.

[0021] In some other embodiments, in step (2), the temperature of the hydrothermal reaction is 180-200° C., and the hydrothermal time is 20-24 h;

[0022] The drying temperature is 50-60° C., and the drying time is 10-12 hours.

[0023] In some other embodiments, in step (3), the pyrolysis conditions are: N2 as protective gas, calcination at 700-750°C for 3-5h, and a heating rate of 2-5°C / min.

[0024] In a third aspect, the present invention provides an application of the catalyst described in the first aspect in wastewater treatment, wherein the application is an application in catalyzing the degradation of 4-hydroxy-3-nitrophenylarsonic acid by activating persulfate.

[0025] In a fourth aspect, the present invention provides a method for catalytic degradation of 4-hydroxy-3-nitrophenylarsonic acid, using the catalyst-activated persulfate described in the first aspect to catalytically degrade 4-hydroxy-3-nitrophenylarsonic acid.

[0026] In some other embodiments, the concentration of the sulfate is 0.05-0.5 g / L, preferably, the concentration of the sulfate is 0.3 g / L;

[0027] The addition amount of Fe3O4@NS4C catalyst was 0.1-0.5 g / L; the initial pH was 3-11;

[0028] Preferably, the addition amount of Fe3O4@NS4C catalyst is 0.2 g / L; and the initial pH is 3-5.5.

[0029] In some other embodiments, the concentration of ROX is 10-15 mg / L, and the reaction time is 30-60 min;

[0030] Preferably, the concentration of ROX is 10 mg / L and the reaction time is 30 min.

[0031] Beneficial effects:

[0032] Compared with the prior art, the present invention has the following advantages:

[0033] (1) The Fe3O4@NS4C catalyst provided by the present invention has polyhedral Fe3O4 nanoparticles uniformly distributed in the flexible carbon chamber, in the form of carbon chamber coating. The Fe ion leaching rate is 80.55ug / L, which is far lower than the current drinking water quality standard in my country (0.3mg / L, GB 5749-2022); it has good magnetic properties and is easy to recycle; it has good cycle stability, and the ROX degradation efficiency is still about 90% after the third continuous cycle. After 4 cycles, if it is thermally regenerated at 350°C, its catalytic performance is basically restored.

[0034] (2) The Fe3O4@NS4C catalyst provided by the present invention is prepared by a hydrothermal method and a pyrolysis method. The preparation process is simple and easy to operate, the preparation process is green and clean, the preparation conditions are easy to control, the preparation cost is low, and it can be prepared on a large scale.

[0035] (3) The Fe3O4@NS4C catalyst provided by the present invention benefits from the confinement advantage of the carbon chamber and the sp 2 The synergistic effect of -C, oxygen-containing groups, N, S doped species and Fe3O4 nanoparticles has a strong ability to activate PMS and can achieve effective removal of ROX. The degradation rate of ROX can reach 95.1% within 30 minutes. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 SEM images of catalyst 1 (a) prepared in Example 1 of the present invention and catalyst 1 (b) prepared in Comparative Example 1;

[0037] Figure 2 This is a schematic diagram of the model structure of the catalyst prepared in Example 1 of the present invention;

[0038] Figure 3 The electrochemical impedance diagrams of the catalysts prepared in Example 1 of the present invention and Comparative Examples 1-3;

[0039] Figure 4The catalyst system prepared in Example 1 of the present invention and Comparative Examples 1-3 activates persulfate to degrade ROX;

[0040] Figure 5 This is a magnetic test of the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The raw materials and reagents used in the following examples are all conventional commercially available products and can be purchased.

[0042] The present invention is described in more detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0043] 1. Preparation of Catalyst

[0044] Example 1

[0045] The preparation method of Fe3O4@NS4C catalyst is as follows:

[0046] (1) Dissolve 0.9 g of ferric sulfate heptahydrate, 0.315 g of hexamethylenetetramine, and 0.315 g of glucose in 40 mL of deionized water and stir rapidly. Mark this solution as a.

[0047] Dissolve 2.24 g of thiophenedicarboxylic acid in 25 mL of N,N-dimethylformamide solution and stir rapidly to form a transparent solution b;

[0048] Solution b was added dropwise into solution a, and the mixture was stirred vigorously at room temperature for 30 min to obtain a mixed solution.

[0049] (2) The mixed solution was transferred to a 100 mL reactor, subjected to hydrothermal reaction at 180° C. for 24 hours, washed by centrifugation with alcohol and deionized water, and then dried in an oven at 60° C. for 12 hours to obtain a precursor.

[0050] (3) The precursor was placed in a high-temperature tube furnace, N2 was used as the protective gas, and calcined at 700°C for 3 h at a heating rate of 2°C / min. The resulting black powder was named Fe3O4@NS4C catalyst.

[0051] Figure 1 (a) is the scanning electron microscope (SEM) image of the prepared Fe3O4@NS4C catalyst. It can be seen that the polyhedral Fe3O4 nanoparticles are evenly distributed in the flexible carbon chamber.

[0052] Figure 2The schematic diagram of the model structure of the prepared Fe3O4@NS4C catalyst shows that the carbon chamber is a multi-porous carbon structure co-modified with flexible N and S. The carbon pore structures contain reserved gaps and are interconnected. The carbon chamber contains multi-atom active sites. The Fe3O4 nanoparticles are evenly distributed in the carbon chamber co-modified with flexible N and S, showing a monodisperse state. This is conducive to giving full play to the confinement advantages of the carbon chamber and the sp 2 The synergistic effect of -C, oxygen-containing groups, N, S doping species and Fe3O4 nanoparticles has a strong ability to activate PMS.

[0053] like Figure 3 From the electrochemical impedance spectroscopy (EIS) of the prepared Fe3O4@NS4C catalyst, it can be seen that the arc radius of the Fe3O4@NS4C catalyst is the smallest, which is attributed to the synergistically enhanced conductivity and electron transport of the four elements Fe, C, N, and S. This shows that in the catalyst Fe3O4@NS4C prepared in Example 1, the carbon chamber is graphite carbon and has strong conductivity.

[0054] Embodiment 2-5

[0055] The preparation methods of Examples 2-5 are the same as those of Example 1, except that a series of different nitrogen-sulfur co-modified carbon chamber-coated iron-based catalysts are controllably synthesized by adjusting the added molar ratio of each raw material in Example 1.

[0056] Table 1 Addition molar ratio of raw materials in Examples 2-5

[0057]

[0058] Comparative Example 1

[0059] Preparation of Fe3O4@NS4 catalyst

[0060] The difference from Example 1 is that in step (1), glucose is not added, and the other preparation processes are the same as those in Example 1 to prepare Fe3O4@NS4 catalyst.

[0061] Figure 1 (b) is the scanning electron microscope (SEM) image of the prepared Fe3O4@NS4 catalyst, where only polyhedral Fe3O4 nanoparticles can be observed.

[0062] like Figure 3 This is the electrochemical impedance spectroscopy (EIS) of the prepared Fe3O4@NS4 catalyst.

[0063] Comparative Example 2

[0064] Preparation of Fe3O4@C catalyst

[0065] The difference from Example 1 is that in step (1), hexamethylenetetramine and thiophene dicarboxylic acid are not added, and the other preparation processes are the same as those in Example 1 to prepare Fe3O4@C catalyst.

[0066] like Figure 3 This is the electrochemical impedance spectroscopy (EIS) of the prepared Fe3O4@C catalyst.

[0067] Comparative Example 3

[0068] Preparation of Fe3O4 catalyst

[0069] The difference from Example 1 is that in step (1), glucose, hexamethylenetetramine and thiophene dicarboxylic acid are not added, and the other preparation processes are the same as those in Example 1 to prepare Fe3O4 catalyst.

[0070] like Figure 3 This is the electrochemical impedance spectroscopy (EIS) of the prepared Fe3O4 catalyst.

[0071] from Figure 3 It can be seen that the arc radius of the catalysts in Example 1 and Comparative Example 2 is significantly smaller than that in Comparative Example 1 and Comparative Example 3, which confirms that the graphitized carbon chamber can effectively promote charge transfer during the catalytic reaction.

[0072] 2. Catalytic performance test

[0073] (1) The catalytic performance of the prepared catalyst was tested under the following test conditions:

[0074] The catalyst prepared by the present invention is added to a ROX aqueous solution (volume 100 mL) with a concentration of 10-15 mg / L, and the rotation speed is 200 rpm and the temperature is 25° C. in a constant temperature shaker. The degradation experiment is started by adding PMS (persulfate). Samples are collected at regular intervals, and after the samples are filtered through a 0.22 μm polytetrafluoroethylene membrane, an equal volume of sodium thiosulfate is added to terminate the reaction.

[0075] Unless otherwise specified, the catalytic performance test in the present invention was carried out at an initial pH of 5.5, and all experiments were conducted in triplicate. The concentration of ROX was measured by high performance liquid chromatography. The degradation rate of ROX was calculated as follows:

[0076] Degradation rate = C t / C0×100%

[0077] Among them, C t is the concentration of ROX at time t; C0 is the concentration of ROX at the initial time.

[0078] Figure 4 The degradation effects of different catalytic systems on ROX in the present invention are as follows: Figure 4It can be seen that the ability of the catalyst prepared in Example 1 to activate persulfate to degrade ROX is much higher than that of Comparative Examples 1-3, and the degradation rate of ROX in Example 1 reaches more than 90% within 5 minutes.

[0079] The degradation effects of the catalysts prepared in Example 2-5 on ROX are shown in Table 2 below:

[0080] Table 2 Degradation effect of Example 2-5 on ROX

[0081]

[0082] (2) Effect of initial pH on the degradation of ROX by the prepared catalyst

[0083] 200 mg / L of the catalyst prepared in Example 1 and 50 mL of a 10 mg / L ROX solution were placed in a 100 mL plastic shake bottle with a lid, and then 200 mg / L PMS was added to start the degradation experiment. After 20 minutes, a sample was taken and filtered with a 0.22 μm polytetrafluoroethylene membrane, and then an equal volume of sodium thiosulfate was added to terminate the reaction. The initial pH of the solution was adjusted to 3, 5, 7, 9, and 11, respectively, and all experiments were conducted in three parallel experiments. The concentration of ROX was measured by high performance liquid chromatography. The results are shown in Table 3.

[0084] Table 3 Effect of different initial pH on the degradation of ROX by the catalyst prepared in Example 1

[0085] pH 3 5 7 9 11 Degradation rate 76% 92% 93% 93% 99%

[0086] (3) Recyclability of catalyst

[0087] 200 mg / L of the catalyst prepared in Example 1 and 50 mL of 10 mg / L ROX solution were placed in a 100 mL plastic shake bottle with a lid, and then 300 mg / L PMS was added to start the degradation experiment. After 30 minutes, a sample was taken and filtered with a 0.22 μm polytetrafluoroethylene membrane, and then an equal volume of sodium thiosulfate was added to terminate the reaction. The catalytic performance and reusability of the Fe3O4@NSC catalyst were evaluated.

[0088] The study found that the ROX degradation efficiency of the catalyst prepared in Example 1 still reached about 90% after the third continuous cycle, which preliminarily showed that the catalyst had good medium reusability. However, the degradation rate dropped to 80% after the fourth cycle, and the degradation rate of the fifth cycle was 75%. After four cycles, if the catalyst was regenerated by heat at 350°C, its catalytic performance was basically restored.

[0089] Table 4 Recyclability of catalyst

[0090]

[0091]

[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst, characterized in that: include: N, S co-doped porous carbon chamber, and Fe3O4 loaded in the pores and on the surface of the porous carbon chamber.

2. The nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst according to claim 1, characterized in that: The specific surface area of ​​the carbon chamber is 45-50m 2 / g, pore size 3.5-5.0nm.

3. A method for preparing the nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst according to claim 1, characterized in that: The following steps are involved: (1) dissolving ferrous sulfate heptahydrate, hexamethylenetetramine, and glucose in deionized water, and stirring to form a solution a; Dissolve thiophene dicarboxylic acid in N,N-dimethylformamide solution, and stir to form solution b; Add solution b dropwise into solution a, and stir to form a mixed solution; (2) subjecting the mixed solution to a hydrothermal reaction, cooling it to room temperature, filtering, washing, centrifuging, and drying to obtain a Fe3O4@NS4C precursor; (3) The Fe3O4@NS4C precursor is pyrolyzed to obtain the Fe3O4@NS4C catalyst.

4. The preparation method according to claim 3, characterized in that: In step (1), the molar ratio of ferric sulfate heptahydrate: hexamethylenetetramine: glucose: thiophenedicarboxylic acid is (1-1.5): (1-1.5): (0.78-0.8): (4-6); Preferably, the molar ratio of ferric sulfate heptahydrate: hexamethylenetetramine: glucose: thiophenedicarboxylic acid is 1:1:0.78:4; The stirring temperature of the mixed solution is 25-30° C., and the stirring time is 30-60 min.

5. The preparation method according to claim 3, characterized in that: In step (2), the temperature of the hydrothermal reaction is 180-200° C., and the hydrothermal time is 20-24 h; The drying temperature is 50-60° C., and the drying time is 10-12 hours.

6. The preparation method according to claim 3, characterized in that: In step (3), the pyrolysis conditions are: N2 as protective gas, calcination at 700-750°C for 3-5h, and a heating rate of 2-5°C / min.

7. Use of the nitrogen-sulfur co-modified carbon chamber-coated iron-based catalyst according to claim 1 in wastewater treatment, characterized in that: The application is the application in catalyzing the degradation of 4-hydroxy-3-nitrophenylarsonic acid by activating persulfate.

8. A method for catalytic degradation of 4-hydroxy-3-nitrophenylarsonic acid, characterized in that: The nitrogen-sulfur co-modified carbon chamber coated iron-based catalyst described in claim 1 or 2 is dispersed in wastewater containing 4-hydroxy-3-nitrophenylarsonic acid, and the persulfate is activated to catalyze the degradation of 4-hydroxy-3-nitrophenylarsonic acid.

9. The method according to claim 8, characterized in that The concentration of sulfate is 0.05-0.5 g / L, preferably, the concentration of sulfate is 0.3 g / L; The amount of catalyst added is 0.1-0.5 g / L; the initial pH is 3-11; Preferably, the amount of catalyst added is 0.2 g / L; and the initial pH is 3-5.

5.

10. The method according to claim 8, characterized in that The concentration of the 4-hydroxy-3-nitrophenylarsonic acid is 10-15 mg / L, and the reaction time is 30-90 min; Preferably, the concentration of the 4-hydroxy-3-nitrophenylarsonic acid is 10 mg / L and the reaction time is 30 min.